Hubungan Antara Pola Asuh Otoriter dan Kematangan Emosi Dengan Perilaku Agresif Pada Siswa SMP Negeri 2 Medan - Rida Kurniati; Asih Menanti; Suryani Hardjo (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2019)
This research aimed to examine the relationship between authoritarian parenting style and emotional maturity with student’s  aggressive behavior. The subject of this research is students grade VIII in SMP Negeri 2 Medan as many as 60. Data analisys was used multiple linear regression.The result of this research showed that : (1) There is  correlation authoritarian parenting style with aggressive behavior, with coefficient   rx1y = 0.384, p = 0.001. It means  higher authoritarian parenting style then it will be the higher aggressive behavior. The effectice contribution is 14.7% and remaining 85,3% is influenced by other factors not examined.    (2) There is no  correlation  emotional    maturity with aggressive behavior, with coefficient  rx2y = 0.358,         p = 0.003. It means  lower emotional maturity no significantly followed by the high aggressive behavior. (3) There is  correlation betweeen authoritarian parenting style and emotional maturity with aggressive behavior, with coefficien  r = 0.449;  p = 0.002   with p 0,010. It means authoritarian parenting style and emotional maturity influence aggressive behavior with effectice contribution is 20,20%.